Strategy of giving concentrate to lactating Holstein cows grazing coast-cross pasture - Alvim, Maurilio José; Verneque, Rui da Silva; Vilela, Duarte; Cóser, Antonio Carlos; Brotel, Milton de Andrade; Rezende, Gisele Maria (Pesquisa Agropecuaria Brasileira, 1999)
The trial was carried out at the Embrapa-Centro Nacional de Pesquisa de Gado de Leite, at Coronel Pacheco, Brazil, to evaluate two ways of feeding 6 kg/day of a concentrate mixture to cows grazing a coast-cross pasture: A - a fixed amount, and B - a variable amount (9, 6 and 3 kg/cow/day for the first, second, and third stage of lactation). A randomized block design was used with two replications for land grazing area, with the treatments organized in split plots. In the plots, the ways of feeding of distributing the ration concentrate were considered, and in the split plots, the phases of lactation were used. Feeding variable amount of concentrate affected (P< 0.05) pasture stocking rate only in the first stage of lactation. Milk productions were 21.5 (±2.8) and 25.5 (±2.6) kg/cow (P < 0.05), 64.5 (±7.1) and 96.9 (±10.3) kg/ha (P < 0.05) in the first phase of lactation; 19.8 (±2.4) and 20.6 (±2.3) kg/cow (P > 0.05), 93.1 (±10.8) and 94.8 (±10.9) kg/ha (P > 0.05) in the second phase; 14.2 (±2.2) and 13.4 (±2.3) kg/cow (P > 005) and 102.2 (±12.4) and 93.8 (±10.5) kg/ha (P > 0.05) in the last phase, respectively for A and B. The variable dose was the best indicated to supplement Holstein dairy cows in coast-cross pasture.
Keywords: forrage consumption; Cynodon dactylon; grazing; milk production; stocking rate